Management of Islamic Religious Education Learning at SMA Al-Hidayah Medan - Lef Lidia Nengsi (Yayasan Rahmat Islamiyah, 2022)
This study aims to determine how the management of Islamic Religious Education learning at the SMA Al-Hidayah Foundation, Medan. How is the impact of Islamic Religious Education learning management at SMA Al-Hidayah Medan. What are the supporting and inhibiting factors for learning Islamic Religious Education at SMA Al-Hidayah Medan. This type of research is a qualitative description with qualitative methods. Sources of data in this study are primary data obtained by direct observation in the field and secondary data obtained by conducting in-depth interviews with informants. The results of this study stated that: First, Islamic Religious Education Teachers at the SMA Al-Hidayah Foundation in Medan in planning lessons made a syllabus and prepared lesson plans before carrying out teaching and learning activities to serve as a guide in the learning process; Second, the learning activities carried out by the teacher are conducting preliminary activities, conducting core and closing activities; Third, the supporting factors in learning activities at SMA Al-Hidayah Medan are appropriate teaching methods, a supportive school environment, individual student interests, and support from both parents. In addition, the inhibiting factors in learning activities at SMA Al-Hidayah Medan are the individual maturity of students and lack of communication, as well as the lack of teacher ability in delivering subject matter, lack of facilities and infrastructure.